OSTRACODOS ORDOVICICOS DE LA PRECORDILLERA DE SAN JUAN (HOJA 18e - SAN JOSE DE JACHAL) (Ameghiniana, 2013)
A new Ordovician Ostracoda fauna, from Los Azules Formation (Precordillera of San Juan), is described in this paper. The silicífíed studied material was found in limestones and it has excellent conservation conditions. We can assume that this association belongs to the Uandeillan-Caradocian because the three genus previously considered, belong to the Middle Ordovician in the northerm hemisphere. One genus reaches Carboniferous times and the others the Upper Ordovician. Furtherrnore we have the age provided by Porterfieldia jachalensis, Harr.·and Leanza. (endemic genus from Precordillera). Nevertheless the authors consider the possibility of a Middle Ordovician age for this fauna.